HUBUNGAN ANTARA MINAT DENGAN MOTIVASI MEMILIH SEKOLAH PADA SISWA SMP NEGERI 1 KRAYAN KALIMANTAN TIMUR - Nova Devisanti; Titik Muti’ah (JURNAL SPIRITS, 2014)
AbstractThe purpose of this study is to determine the relationship between the interest and motivation of choosing senior high schools. Subjects in this study were students in 1 Krayan East Kalimantan, with the purposive sampling technique. The method of analysis used in this study is Product Moment .Motivation variable data analysis choosing a school with a variable interest in showing the value of r =0.475 with a significance level of p =0.000. There is a significant positive relationship between interest and motivation in students choosing school SMP Negeri 1 Krayan. The determinant coefficient of 0.225, meaning interest variable contribute effectively in motivating choose schools as 22.5 %, while the remaining 77.5 % is influenced by other factors such as the intrinsic factor consisting of passion and desire to succeed, hopes and ideals of extrinsic factors that consists of awards in learning, conducive learning environment and engaging learning activities .Keywords: Interests, Motivation Choosing Schools.